2010
DOI: 10.1111/j.1465-7287.2010.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Workplace Employer-Sponsored Training in Canada: Role of Firm Characteristics and Worker Attributes

Abstract: In this work, we study the role of firm characteristics and worker attributes in determining participation in workplace employer‐sponsored training in Canada using the Workplace and Employee Survey (WES) of Statistics Canada. We attempt to answer the following questions using the rich information of firms that are available in WES data: Does firms' provision of workplace training encourage workers' participation in Canada? How do changes in market competition, organizational changes, and technological innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 45 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…Similar to elsewhere, Canadian females tend to have relatively poor working conditions compared with their male counterparts (Cranford et al ., 2003; Zeytinoglu et al ., 2003), including lower access to employer‐supported training (Knoke & Ishio, 1998; Lowe & Krahn, 1995). Admittedly, a few studies (such as Turcotte et al ., 2003; Xu & Lin, 2007) suggest that females have similar or even slightly better access to training than males. In terms of age, studies consistently show that older workers participate less in training (see, e.g., Peters, 2004; Xu & Lin, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to elsewhere, Canadian females tend to have relatively poor working conditions compared with their male counterparts (Cranford et al ., 2003; Zeytinoglu et al ., 2003), including lower access to employer‐supported training (Knoke & Ishio, 1998; Lowe & Krahn, 1995). Admittedly, a few studies (such as Turcotte et al ., 2003; Xu & Lin, 2007) suggest that females have similar or even slightly better access to training than males. In terms of age, studies consistently show that older workers participate less in training (see, e.g., Peters, 2004; Xu & Lin, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, there appears to be a trend among female workers where those with dependent children received more training during the 1990s, but that gap has now either disappeared or reversed compared with those without dependent children (see Hurst, 2008). Those with significant family responsibilities, such as having dependent children, are thought to face more barriers to training relative to others (see Chaykowski, 2005; Vallée, 2005; Xu & Lin, 2007), and females continue to bear the bulk of family duties in Canada. However, Underhill (2006) found an insignificant association between training participation and marital status per se.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Workplace and Employee Survey (WES), Zeytinoglu and Cooke () find that workers in firms implementing information technology and those facing competition from foreign firms are more likely to train. Xu and Lin () also employ the WES data and report a positive impact between international competition and participation in employer‐provided training, in addition to a positive link between technological innovation and training incidence. It should be noted that the foreign competition variables used in these studies are developed from self‐reported measures of the perceived degree of foreign competition faced by the firm.…”
Section: Introductionmentioning
confidence: 99%